Level Fatigue of Chronic Kidney Disease Patients Undergoing Hemodialysis - Adiyati Mardiyah; Restu Amalia Azmy (Journal of Applied Nursing and Health, 2022)
Background: The hemodialysis process is beneficial for chronic kidney disease patients in maintaining their lives. This routine and the continuous process will cause complications in the body. Fatigue is the main complaint of patients undergoing long-term hemodialysis. Fatigue conditions in patients with chronic kidney disease appear to be caused by physiological and psychological factors. The fatigue condition in the client will affect the patient's daily activity level. Methods: This research is a descriptive study with a cross-sectional study design. The sample in this study was 78 patients undergoing hemodialysis who were taken using the purposive sampling technique—assessment of Fatigue using the PSF (Piper Fatigue Scale) questionnaire. Data analysis in this study used descriptive analysis to determine the variables' distribution, frequency, and percentage. Results: From the research results, some respondents do not work by 92.3%. Several reasons cause them not to work again since chronic kidney disease. One of the reasons is that they feel tired quickly, so their activity is limited, and some patients feel that they are limiting their activities because they have an av shunt attached. Based on the results of the study that most of the respondents had undergone the HD process for 2-4 years (78.8%). The highest Hb values were in the range of 9-10gr/dl (88.4%). Conclusion: Fatigue of patients undergoing hemodialysis increases. it is hoped that respondents can know and increase their level of self-efficacy after being vaccinated against covid-19